SOSIALISASI PROTOKOL KESEHATAN DALAM UPAYA PENCEGAHAN PENYEBARAN COVID-19 KEPADA MASYARAKAT PESISIR NATUNA - Muhardi Muhardi; Risko Risko; Riza Adriat; Mega Sari Juane Sofiana; Suhardi Irawan; Jannati Jannati (Universitas Teuku Umar, 2021)
Corona Virus Disease 2019 (Covid-19) is an infectious disease that infects the respiratory tract. The spread of the Covid-19 infectious disease outbreak was so fast that it reached the territory of Indonesia, including in one of the coastal areas of Natuna Regency, Riau Islands Province. The purpose of this community service activity is to socialize the Covid-19 community in the coastal area of Pangkalan Village, Serasan District, Natuna Regency, Riau Islands Province, and Bandarsyah Village, Natuna Islands in an effort to prevent the spread of Covid-19 and increase public awareness about the dangers of Covid-19. This community service activity went smoothly and received a very good response and support from village officials and the local community. The results of this activity provide information on the importance of maintaining health protocols to increase awareness about the dangers of Covid 19 and also the distribution of basic necessities to people in need. This is indicated by the enthusiasm of the community to participate in this activity.